A systematic review and meta-analysis on the association of serum and tumor tissue iron and risk of breast cancer - Akram Sanagoo; Faezeh Kiani; Marzieh Saei Gharenaz; Fatemeh Sayehmiri; Fatemeh koohi; Leila Jouybari; Majid Dousti (Babol University of Medical Sciences, 2020)
Background: Some studies have investigated the effects of iron on breast carcinogenesis and reported different findings about the association between Fe and breast cancer risk. This study was conducted to estimate this effect using meta-analysis method. Methods: A total of 20 articles published between 1984 and 2017 worldwide were selected through searching PubMed, Scopus, Embase, Web of Science, and Cochrane Library. Keywords such Breast Cancer, Neoplasm, Trace elements, Iron, Breast tissue concentration, Plasma concentration, Scalp hair concentration, toenail concentration and their combination were used in the search. Results: The total number of participants was 4,110 individuals comprising 1,624 patients with breast cancer and 2,486 healthy subjects. Fe concentration was measured in the various subgroups in both case and control groups. There were significant correlations between Fe concentration and breast cancer in breast tissue subgroup (SMD: 0.67 [95% CI: 0.17 to 1.17; P=0.009]). Whereas, there was no meaningful difference in Fe status between women with and without breast cancer related to scalp hair and plasma subgroups; (SMD: -3.74 [95% CI: -7.58 to 0.10; P=0.056] and (SMD:-1.14[95% CI: -2.30 to 0.03; P=0.055], respectively. Conclusion: The present meta-analysis indicated a positive and straight association between iron concentrations and risk of breast cancer but because of high heterogeneity we recommend more accurate future studies